1999
DOI: 10.1021/bi991661f
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Redox Potential of the [Fe(SCys)4] Site in Rubredoxin by the Orientation of a Peptide Dipole

Abstract: Rubredoxins (Rds) may be separated into two classes based upon the correlation of their reduction potentials with the identity of residue 44; those with Ala44 have reduction potentials that are approximately 50 mV higher than those with Val44. The smaller side chain volume occupied by Ala44 relative to that occupied by Val44 has been proposed to explain the increase in the reduction potential, based upon changes in the Gly43-Ala44 peptide bond orientation and the distance to the [Fe(SCys)(4)] center in the Pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(132 citation statements)
references
References 35 publications
7
125
0
Order By: Relevance
“…The average k obs of ϳ240 s Ϫ1 coupled with the C13S 2Fe-SOR blue concentration of 200 M used in these experiments leads to an estimated second-order rate constant of 1.2 ϫ 10 6 M Ϫ1 s Ϫ1 for the reduced rubredoxin/C13S 2Fe-SOR blue electron transfer reaction. The fact that this value is about 4 times greater than the previously reported electron self-exchange rate constant for rubredoxin, ϳ3 ϫ 10 5 M Ϫ1 s Ϫ1 , can be qualitatively rationalized by the ϳ300 mV driving force for the reduced rubredoxin/ oxidized 2Fe-SOR electron transfer reaction (12,32) and the protein-surface accessible, solvent-exposed [Fe(His) 4 (Cys)] site of 2Fe-SOR (10). The limited amounts of C13S 2Fe-SOR available and the rapidity of the reaction prevented a more thorough kinetic analysis.…”
Section: The Superoxide Reductase Catalytic Cyclementioning
confidence: 69%
“…The average k obs of ϳ240 s Ϫ1 coupled with the C13S 2Fe-SOR blue concentration of 200 M used in these experiments leads to an estimated second-order rate constant of 1.2 ϫ 10 6 M Ϫ1 s Ϫ1 for the reduced rubredoxin/C13S 2Fe-SOR blue electron transfer reaction. The fact that this value is about 4 times greater than the previously reported electron self-exchange rate constant for rubredoxin, ϳ3 ϫ 10 5 M Ϫ1 s Ϫ1 , can be qualitatively rationalized by the ϳ300 mV driving force for the reduced rubredoxin/ oxidized 2Fe-SOR electron transfer reaction (12,32) and the protein-surface accessible, solvent-exposed [Fe(His) 4 (Cys)] site of 2Fe-SOR (10). The limited amounts of C13S 2Fe-SOR available and the rapidity of the reaction prevented a more thorough kinetic analysis.…”
Section: The Superoxide Reductase Catalytic Cyclementioning
confidence: 69%
“…Redox Potential-To characterize the electrophysiological properties of the cryptomonad rubredoxin, we determined its redox potential under the same conditions as in Eidsness et al (22). Purified recombinant rubredoxin (8) was used to measure the redox potential.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is a crucial amino acid at a conserved position (amino acid residue 44, referring to C. pasteurianum rubredoxin). Site-directed mutagenesis showed that changes from valine to the more polar alanine (and vice versa) correlate with the change of midpoint redox potential (22). Exclusively, the G. theta rubredoxin sequence has a serine at this position.…”
Section: Rubredoxin Is Associated With Psii 30061mentioning
confidence: 99%
“…Ultrapure urea and guanidine hydrochoride (GuHCl) were from Sigma. CpRds and PfRds were expressed and purified as the ironcontaining holoRds according to published procedures [29]. Unless otherwise indicated, all the experiments were carried out aerobically at room temperature in 50 mM tris(hydroxymethyl)aminomethane hydrochloride, pH 7.4 (hereafter referred to as buffer).…”
Section: Proteins Chemicals and General Proceduresmentioning
confidence: 99%
“…Stock solutions of 6-8 M urea or 6 M GuHCl were prepared in buffer. The concentrations of holoRds were determined using ε 492 = 8,850 M −1 cm −1 [23,29]. ApoCpRd and apoPfRd were prepared by treating the holoRds with 10 or 25% trichloroacetic acid, respectively, in the presence of 5 mM 2-mercaptoethanol at 0 °C.…”
Section: Proteins Chemicals and General Proceduresmentioning
confidence: 99%